Serum C-reactive protein predicts early mortality in hospitalized patients with HBV-related decompensated cirrhosis - Zhu, ShaoMing (Medicine (Baltimore), 2017)
The serum C-reactive protein (CRP) is an inflammatory marker. The aim of the present study was to elucidate whether CRP could serve as a potential surrogate marker for 30-day mortality in hospitalized patients with HBV-related decompensated cirrhosis (HBV-DeCi). This was a retrospective cohort study that included 140 patients with HBV-DeCi. All patients were followed up for 1-month. A panel of clinical and biochemical variables were analyzed for potential associations with outcomes using multiple regression models. The serum CRP was significantly higher in nonsurviving patients than in surviving patients. Multivariate analysis demonstrated that CRP levels (odds ratio: 1.047, P = 0.002) and the model for end-stage liver disease score (odds ratio: 1.370, P = 0.001) were independent predictors for mortality. Serum CRP is a simple marker that may serve as an additional predictor of 1-month mortality in hospitalized patients with HBV-DeCi.